Work, retirement and physical activity: cross-sectional analyses from the Whitehall II study - Gill Mein; Martin J. Shipley; Melvyn Hillsdon; George T. H. Ellison; Michael Marmot (2005)
Background: To explore the relationship between work, retirement and physical activity. Methods: Cross-sectional analyses of data from self-completed questionnaires by 6224 civil servants aged 45–69 years participating in phase 5 of the Whitehall II longitudinal study. Results: There appeared to be a dose–response relationship between hours worked and the prevalence of physical activity, with a lower prevalence of recommended physical activity amongst participants working full time (≥30 h/week), higher prevalence rates amongst those working part time (<30 h/week), and the highest rates amongst participants who were not working at all. Physical activity rates did not increase greatly amongst study participants who had retired from the Civil Service but had gone on to do further full-time work, however, the higher physical activity rates of participants working part time, or not at all, were further enhanced amongst those who had also retired. Conclusions: These findings suggest that full-time work is associated with lower rates of recommended physical activity levels in this cohort of middle-aged white-collar office workers. Lower grade occupations are also less likely to meet the recommended physical activity levels. While retirement is associated with higher rates of recommended physical activity levels, this benefit is evident amongst those who work part time, or not at all, during their retirement, for whom the benefits of retirement and lower working hours on rates of physical activity appear additive. The frequency of different types of physical activity is associated with different occupational grades, with more sport and gardening being done by the higher occupational grades. Key points